Heart Rate Signal Decomposition - Mizuta, H.; Yana, K. (Methods of Information in Medicine, 2000)
This paper proposes a method for decomposing heart rate fluctuations into background, respiratory and blood pressure oriented fluctuations. A signal cancellation scheme using the adaptive RLS algorithm has been introduced for canceling respiration and blood pressure oriented changes in the heart rate fluctuations. The computer simulation confirmed the validity of the proposed method. Then, heart rate fluctuations, instantaneous lung volume and blood pressure changes are simultaneously recorded from eight normal subjects aged 20-24 years. It was shown that after signal decomposition, the power spectrum of the heart rate showed a consistent monotonic 1/fa type pattern. The proposed method enables a clear interpretation of heart rate spectrum removing uncertain large individual variations due to the respiration and blood pressure change.
Keywords: Heart Rate Fluctuations; 1/f Fluctuations; Instantaneous Lung Volume; Blood Pressure; Spectral Analysis; Adaptive Signal Processing; RLS Algorithm